Differences between familial and sporadic dilated cardiomyopathy: ESC EORP Cardiomyopathy & Myocarditis registry. (11th November 2020) - Asselbergs, Folkert W.; Sammani, Arjan; Elliott, Perry; Gimeno, Juan R.; Tavazzi, Luigi; Tendera, Michael; Kaski, Juan Pablo; Maggioni, Aldo P.; Rubis, Pawel P.; Jurcut, Ruxandra; Heliö, Tiina; Calò, Leonardo; et al.
Abstract: Aims: Dilated cardiomyopathy (DCM) is a complex disease where genetics interplay with extrinsic factors. This study aims to compare the phenotype, management, and outcome of familial DCM (FDCM) and non‐familial (sporadic) DCM (SDCM) across Europe. Methods and results: Patients with DCM that were enrolled in the prospective ESC EORP Cardiomyopathy & Myocarditis Registry were included. Baseline characteristics, genetic testing, genetic yield, and outcome were analysed comparing FDCM and SDCM; 1260 adult patients were studied (238 FDCM, 707 SDCM, and 315 not disclosed). Patients with FDCM were younger ( P  < 0.01), had less severe disease phenotype at presentation ( P  < 0.02), more favourable baseline cardiovascular risk profiles ( P  ≤ 0.007), and less medication use ( P  ≤ 0.042). Outcome at 1 year was similar and predicted by NYHA class (HR 0.45; 95% CI [0.25–0.81]) and LVEF per % decrease (HR 1.05; 95% CI [1.02–1.08]. Throughout Europe, patients with FDCM received more genetic testing (47% vs. 8%, P  < 0.01) and had higher genetic yield (55% vs. 22%, P  < 0.01). Conclusions: We observed that FDCM and SDCM have significant differences at baseline but similar short‐term prognosis. Whether modification of associated cardiovascular risk factors provide opportunities for treatment remains to be investigated. Our results also show a prevalent role of genetics in FDCM and a non‐marginal yield in SDCM although genetic testing is largely neglected in SDCM. Limited genetic testing and heterogeneity in panels provides a scaffold for improvement of guideline adherence.